Modificação física de amido de mandioca para elaboração de pão de queijo com extrato de erva-mate e seu efeito nas propriedades tecnológicas, funcionais e sensoriais - Kazerski, Rosemeri Teresinha da Silva (2020)
Starch extracted from plants without alteration is called native, however, present some disadvantages, such as insolubility in cold water, loss of viscosity and a tendency to retrogradation. Thus, the food industry has been developing new products with specific functional properties, able to withstand the adverse conditions of processing, called modified starches. Also, the preference for products without adding chemicals in their composition has increased, the use of physically modified starch is encouraged. Moreover, the addition of bioactive compounds in foodstuffs has been researched and developed. Yerba mate can be used for this purpose , since the leaves have several substances beneficial to the human health such as phenolic compounds, known for antioxidant and anti-inflammatory action. Cheese bread is a product that allows the elaboration with the inclusion of yerba mate extract and to avoid the loss of bioactive compounds, modified starch was used. This study aimed to evaluate the physical modification of cassava starch through heat-moisture treatment (HTM) by using different moisture contents during the modification and to evaluate the influence of the addition of yerba mate extract on the functional and technological properties of cheese breads. The study was divided into two experiments: in experiment 1 the cassava starch was modified by HTM at 30%, 38%, 44% and 50% moisture and the pasta properties, texture profile analysis, swelling power, solubility and technological properties of cheese breads compared with commercially modified starch were evaluated. In experiment 2, the modified starch with the best characteristics was used for addition of yerba mate extract into cheese bread. For this, the water of formulation was replaced by yerba mate extract at concentrations of 100%, 75%, 50%, 25% and 0%. Cheese breads with the addition of yerba mate were characterized by chemical composition, phenolic compounds, antioxidant activity, functional groups, thermogravimetric analysis, and also sensory analysis of cheese bread. HTM modification with 44% moisture presented gelatinization profile closer to commercial starch, with reduction of final viscosity and retrogradation besides presenting cold viscosity. Cheese breads prepared with starches modified by HTM showed increased firmness, however starch with HTM 44% showed firmness maintenance until 4 h after the foraking. The addition of yerba mate extract improved the expansion index, presented phenolic compounds and antioxidant activity relevant up to the 50% extract addition index, and above this value acted with pro-oxidant showing reduction in antioxidant activity. In relation to the sensory analysis, the cheese bread presented good acceptability, so the cheese bread with the addition of yerba mate extract can be classified as a functional food